Tensor Product and Certain Solutions of Fractional Wave Type Equation (European Journal of Pure and Applied Mathematics, 2021)
In this paper we Ond certain solutions of some fractional partial diÂ§erential equations. Tensor product of Banach spaces is used to Ond some solutions where separation of variables does not work. We solve the fractional wave type equation using fractional Fourier Series